IDENTIFIKASI BAKTERI PADA SAUS TOMAT YANG DIGUNAKAN PENJUAL BAKSO BAKAR DISEKITAR KAMPUS UNIVERSITAS RIAU SEBAGAI RANCANGAN MODUL PEMBELAJARAN BIOLOGI DI SMA - Nurhasanah '; Irda Sayuti; Evi Suryawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The study was conducted to identification of bacteria on the tomato sauce which used by grilled meatballs seller around the University of Riau as design module biology learning in senior high school in March and April 2016. The results are used for designing learning modules on subjects biology. This research was conducted in two stages: stage of laboratory research and design phase of learning modules. This research is descriptive and conducted by examination in the laboratory. The sampling technique in this study, done by using purposive sampling method. The results showed that the isolated bacteria found in tomato sauce before uses consists of three genera namely the genus Bacillus, Enterobacter and Pseudomonas. The isolated bacteria found in tomato sauce after uses consists of three genera namely the genus Bacillus, Enterobacter and Pseudomonas. The results of this study can be used as a learning module design in high school biology in order to enrich the teaching materials on the concept of bacterial characteristics eubacteria.